Financial preparedness for retirement among private sector employees in the Klang Valley, Malaysia - Krishnan, Swaarna (2019)
Being financially prepared for retirement is challenging due to escalating cost of living and slower movement of labour income. This means people have a lower pay and eventually lack of EPF accumulation. This is made worst by poor money management and the need for more funds for retirement because people live longer. Failing to do so will increase vulnerability, so proper plan must be put in place. The objective of the study is to understand financial planning behaviour for retirement, to measure EPF fund adequacy and to examine their self-rated retirement assessment. The fourth and fifth objective is to develop a typology and assessing the probability of financial preparedness of respondents respectively. The final objective is to explore factors that motivate or hinders financial preparedness for retirement. The theoretical basis of this study will be The System Theory and Life-Cycle Model. This study utilized a secondary data and supplemented with a focused group discussion (FGD). A total of 324 were selected out of 754 respondents from the data. 15 informants consisting of private sector employees were chosen for the FGD. Parametric statistical techniques and thematic analysis were used to analyze the quantitative and qualitative data respectively. Finding from the study indicated that, respondents had good behavior towards retirement preparedness. EPF was not adequate and respondents overrated themselves for retirement preparedness. The typology shows four (4) naturally formed clusters consist of respondents who has the effort for retirement, adequate EPF and vice versa. The findings from multinomial logistic shows respondents who are female, older employees, non-Malays, married, has tertiary level education and M40 group are more prepared for retirement.Respondents were categorized in each clusters and the common characteristics they have, hence this is a better way for the financial educators or government to help them in the area they need.